Anti-stroke biologics: from recombinant proteins to stem cells and organoids - Shu-Na Wang; Chao-Yu Miao; Zhi Wang; Zhu-Wei Miao; Si-Li Zheng (Stroke and Vascular Neurology)
The use of biologics in various diseases has dramatically increased in recent years. Stroke, a cerebrovascular disease, is the second most common cause of death, and the leading cause of disability with high morbidity worldwide. For biologics applied in the treatment of acute ischaemic stroke, alteplase is the only thrombolytic agent. Meanwhile, current clinical trials show that two recombinant proteins, tenecteplase and non-immunogenic staphylokinase, are most promising as new thrombolytic agents for acute ischaemic stroke therapy. In addition, stem cell-based therapy, which uses stem cells or organoids for stroke treatment, has shown promising results in preclinical and early clinical studies. These strategies for acute ischaemic stroke mainly rely on the unique properties of undifferentiated cells to facilitate tissue repair and regeneration. However, there is a still considerable journey ahead before these approaches become routine clinical use. This includes optimising cell delivery methods, determining the ideal cell type and dosage, and addressing long-term safety concerns. This review introduces the current or promising recombinant proteins for thrombolysis therapy in ischaemic stroke and highlights the promise and challenges of stem cells and cerebral organoids in stroke therapy.